"The Waiapu Saint of old" : a re-evaluation of William Colenso's legacy and theology in the Waiapu Diocese : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University [EMBARGOED UNTIL FURTHER NOTICE] - Reid, Joshua (Massey University, 2016)
The Reverend William Colenso F.R.S., F.L.S is acknowledged as an important, controversial and deeply uncomfortable figure in the history of the Anglican Diocese of Waiapu. Waiapu is a diocese that now prides itself on progressiveness and liberality. The church considers Colenso’s civic, scientific and political achievements to be the redeeming features of this conservative, legalistic and overbearing evangelical, who became a great hypocrite through an illicit sexual relationship with a Māori “girl”. In 1852 Colenso was dismissed from the church and the Church Missionary Society, and was deprived of Holy Orders. Forty years later he was restored as a deacon. Historians have acknowledged, in varying degrees, the nature of Colenso’s personal faith but the development of his theology, churchmanship and reactions to the changes in the church between 1852 and 1892 have not been sufficiently chronicled. The path by which he came to re-gain the respect of the church and be restored to its favour also has not been comprehensively explored, nor has this journey been fully understood by the diocese he came to re-enter over a century ago. This thesis will examine the ecclesiastical politics and rehabilitation of William Colenso as an Anglican minister. It will also analyse the way in which his academic and civic work informed the development of his churchmanship and theology, and how his new understandings sat in the wider Anglican context and were received in the Diocese of Waiapu.
Keywords: Colenso, W. (William), 1811-1899; Church of the Province of New Zealand -- Diocese of Waiapu -- History; Waiapu (N.Z.) -- Church history